TÜRKLERDEKİ HOŞGÖRÜNÜN DİNİ TEMELLERİ - TÖYER, TUBA (Fırat Üniveristesi, 2004)
"Türklerdeki Hoşgörünün Dini Temelleri adlı çalışmamız giriş ve iki bölümden oluşmaktadır. Giriş kısmında Türk adı, Türk soyu, Türklerin anayurdu, göçleri, Türklerin kültürel ve idari yapıları ile ahlâki özellikleri hakkında bilgi verilmiştir. Birinci bölümde İslamiyet'ten önce Türklerdeki dini yapı ele alınmış ve İslamiyet'ten önce kurulan Türk devletlerindeki hoşgörü anlayışının dini temelleri incelenmiştir. İkinci bölümde ise, Türklerin İslamiyet'i kabul etmeleri ve İslamiyet'ten sonra kurulan Türk devletlerindeki hoşgörü anlayışının dini temelleri incelenmiştir. Bu çalışma bibliyografya kısmıyla sona ermektedir.

Our study, which is called "The Religious Basis of Indulgence in Turks" consists of an introduction and two other parts. In the introduction part some information is given about the Turkish name, the Turkish race, the homeland of the Turks, cultural and administrative structure and the moral properties of the Turks. In the first part, the religious structure before the Islamism is taken up and the religious basis of indulgence understanding in the pre- Islam states is investigated. And in the second part, acceptance of Islam and the religious basis of indulgence understanding in the Turkish states which were established after the acceptance of the Islam are investigated. This study is ended with bibliography parts.
The religious basis of indulgence in Turks
Keywords: Din; Religion; Halk Bilimi (Folklor); Folklore; Sosyoloji; Sociology